Preparation and characterization of a chitosan film with grape seed extract-carvacrol microcapsules and its effect on the shelf-life of refrigerated Salmon (Salmo salar) - Alves, Vera Lúcia da Conceição Duarte; Rico, Bruna P. M.; Cruz, Rui; Vicente, António A.; Khmelinskii, Igor; Vieira, Margarida (LWT, 2018)
Chitosan films with grape seed extract and carvacrol microcapsules (CMF) were prepared and their physico-chemical properties and effect on physico-chemical and microbiological parameters in refrigerated salmon were tested. CMF showed higher values of thickness (0.41 ± 0.04 mm), moisture content (13 ± 1 g water/100 g film), a (11 ± 3), b (12 ± 3), opacity (20 ± 1%), water vapor permeability (WVP) (4.4 ± 0.4) × 10−10 gPa−1s−1m−1, oxygen permeability (O2P) (1.3 ± 0.3) × 10−12 gPa−1s−1m−1 and carbon dioxide permeability (CO2P) (1.3 ± 0.3) × 10−12 gPa−1s−1m−1 as compared to those of the chitosan control film (CCF). CMF showed lower values of L (66 ± 5) and water solubility (17 ± 1%). The salmon packed into CMF presented on the 7th day of storage a lower value of TVB-N (37 ± 4 mg N/100 g fish) as compared to the CCF (42 ± 3 mg N/100 g fish) and control samples (CS; 66 ± 7 mg N/100 g fish). The CMF showed lower values of pH and lightness after 7 days of storage as compared to CS and CCF. The CMF showed also lower values of mesophilic and psychrophilic bacteria and Pseudomonas spp, reaching the maximum limit allowed for the first two only on the 7th day of storage. CMF increases the shelf-life of refrigerated salmon to 4–7 days of storage due to the antimicrobial effect of the natural agents. SFRH/BPD/70036/2010 info:eu-repo/semantics/publishedVersion